SOSIALISASI DAMPAK INFESTASI Pediculosis capitis DI BATURONO KALURAHAN JOYOSURAN KECAMATAN PASAR KLIWON - Haryatmi, Dwi; Janah Sayekti, Fitria Diniah (Journal of Dedicators Community, 2022)
Pediculosis capitis is an infestation of Pediculus humanus var. Capitis or commonly called head lice on the hair and scalp of humans. The disease has become endemic worldwide both in developed and developing countries, with most infestations occurring in school-age children. In Indonesia alone cases of pediculosis from 2016 to 2019 are still widely found with a percentage that is still high for example in the provinces of Aceh, Pekanbaru, Pelembang, Medan which is between 21.1% to 80.3%. In Baturono, Joyosuran Village, Pasar Kliwon District from the examination of lice in children found that of 24 children, all had pediculosis. This socialization aims to provide knowledge to the public about lice infestation, its impact and how to prevent it through direct socialization. Socialization was attended by 24 participants of Family Welfare Empowerment (PKK) mothers from 30 invitations sent with postest results of 100% of participants who participated experienced an increase compared to the pretest value. This shows that participants have a better understanding and knowledge of lice infestations and also how to prevent them